Pertumbuhan Jahe Emprit (Zingiber officinale var. Rubrum) setetah Perlakuan Pupuk Kuda - Haryanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
The aims of this experiment was to know thw growth of ginger after treatment horse fertilizer. Randomized Complete Design with 3 replicates were used to the experiment. The dosage was 7lg, 142g,213g, 248g and control (0g). Parameters was sum of leaf, sum of root, length of root and sum of bud. The result of this experiment indicated that horse fertilizer was able to increase on sum of leaf and tusk of length root. Dosage of 213g is better to increase of length of the root.